Changes in Microvascular Morphology in Subcortical Vascular Dementia: A Study of Vessel Size Magnetic Resonance Imaging - Choi, Hyeon-Il; Ryu, Chang-Woo; Kim, Songvin; Rhee, Hak Young; Jahng, Geon-Ho (Frontiers in Neurology, 2020)
Background: Cerebral small vessel disease is the most common cause of subcortical vascular dementia (SVaD). Unfortunately, conventional imaging techniques do not always demonstrate the microvascular pathology that is associated with small vessel disease. The purpose of this study was to evaluate the changes in the microvascular structure of SVaD and to identify how the microvascular changes in vessel size, detected with imaging, affect the gray matter. Methods: Ten SVaD patients and 12 healthy controls underwent vessel size imaging with gradient-echo and spin-echo sequences before and after contrast agent injection. Four microvessel index maps, including total blood volume fraction (BVf), mean vessel density (Q), mean vessel diameter (mVD), and vessel size index (VSI) were calculated. ROI value of each microvessel parameter was compared between SVaD patients and controls. Voxel-wise comparison of microvessel parameters was also performed to assess the regional difference. The relationship between the microvessel parameters in white matter and total gray matter volume (TGV) were assessed. Results: Both mVD and VSI were significantly different between the SVaD and controls in the ROI-based comparisons (unpaired t-test, p < 0.05). mVD and VSI were significantly increased in the SVaD group at the subcortical, periventricular white matter, basal ganglia, and thalami compared with the controls (FDR corrected, p < 0.05). VSI in the white matter areas were significantly negatively correlated with TGV (r = −0.446, p < 0.05). Conclusions: The increase of mVD and VSI in SVaD patients reflects the damage of the microvessels in the white matter, and these changes may lead to the damage of the gray matter.